HDAC6 promotes hepatocellular carcinoma progression by inhibiting P53 transcriptional activity. Issue 7 (10th February 2013) - Ding, Gang; Liu, He-Dai; Huang, Qian; Liang, Hong-Xiang; Ding, Zhao-Han; Liao, Zhi-Jun; Huang, Gang
Abstract : Hepatocellular carcinoma (HCC) is the most common type of liver cancer. HDAC6 is a transcriptional regulator of the histone deacetylase family, subfamily 2. Previous studies have shown that HDAC6 plays critical roles in transcription regulation, cell cycle progression and developmental events. However, its biological roles in the development of HCC remain largely unexplored. In the present study, we found that mRNA and protein levels of HDAC6 were up‐regulated in HCC tissues and cell lines. The proinflammatory cytokines, which were up‐regulated in the human HCC microenvironment, increased HDAC6 expression through a proximal NF‐kappaB binding site on the HDAC6 gene promoter. Furthermore, overexpression of HDAC6 could promote cell proliferation in HCC cell lines. In contrast, HDAC6 knockdown using small interfering RNA inhibited cell proliferation. At the molecular level, we demonstrated that HDAC6 could interact with p53 and attenuate its transcriptional activity through promotion of its degradation. Therefore, our results suggest a previously unknown HDAC6‐p53 molecular network controlling HCC development. Abstract : ► Up‐regulation of HDAC6 is a frequent event in HCC tissues or cells. ► Identification of HDAC6 as a transcriptional target of NF‐κB. ► HDAC6 promotes HCC cell proliferation. ► HDAC6 Physically Interacts with Hdm2 and p53.